An Example Of Kırlangıç (Tüteklikli) Covering House In The Traditional Tunceli Houses - Şen, Korkmaz; Erdoğan, Serkan (Fırat University, 2019)
Traditional house types in different geographical regions of Anatolia were formed by structural aspects shaped by climatic factors, constructive materials, and lifestyles due to belief systems and traditions. For this reason, traditional residential architects are in material culture properties the first to be referred to for the understanding of local cultures. It has a long history in terms of construction techniques kırlangıç (tüteklikli) cover in the east of Anatolia to research the different types of houses, is gaining importance in this context. This study is about a traditional house architecture with a kırlangıç (tüteklikli) covered in the village of Yaşaroğlu (Goman) where is found 30 km east of Mazgirt district of Tunceli province. In terms of incorporating a tandoori house featured with a kırlangıc, the house reflects a different architectural concept within the traditional house architecture in Tunceli. In Tunceli, the fact that such house samples are not subject to any scientific research until now makes this civil building in Yaşaroğlu village more unique. This study aims to introduce the example of a kırlangıç (tüteklikli) covering house in Tunceli and to emphasize the place and its importance in terms of the history of art and architecture.

Anadolu’nun farklı coğrafi bölgelerindeki geleneksel ev tiplerini, iklim özellikleri, yapı malzemeleri, inanç ve gelenekler ile bağlantılı yaşam tarzının biçimlendirdiği yapısal özellikler belirlemiştir. Bu nedenle geleneksel konut mimarileri, yerel kültürlerin anlaşılabilmesinde ilk müracaat edilecek maddi kültür varlıklarındandır. Anadolu’nun doğusunda yapım tekniği bakımından uzun bir geçmişe sahip kırlangıç (tüteklikli) örtü gibi farklı ev tiplerinin araştırılması bu bağlamda önem kazanmaktadır. Bu çalışma Tunceli ili Mazgirt ilçesinin 30 km. doğusunda yer alan Yaşaroğlu (Goman) Köyü’nde tespit edilmiş kırlangıç (tüteklikli) örtülü, geleneksel bir ev mimarisini konu edinmektedir. Kırlangıç (tüteklikli) örtülü bir Tandır evi özelliğini barındırması bakımından söz konusu ev, Tunceli’de yer alan geleneksel konut mimarisi içerisinde farklı bir mimari anlayışı yansıtmaktadır. Tunceli’de bu tür ev örneklerinin şimdiye kadar herhangi bir bilimsel araştırmaya konu olmaması, Yaşaroğlu Köyü’ndeki sivil yapıyı daha özgün kılmaktadır. Bu çalışma ile Tunceli’de yer alan kırlangıç (tüteklikli) örtülü bir ev örneğinin tanıtılması, sanat ve
GELENEKSEL TUNCELİ EVLERİNDE KIRLANGIÇ (TÜTEKLİKLİ) ÖRTÜLÜ BİR KONUT ÖRNEĞİ